A conceptual design for smell based augmented reality: case study in maintenance diagnosis - Wang, Jeff; Erkoyuncu, John Ahmet; Roy, Rajkumar (Elsevier, 2018)
The trend of Industry 4.0 encourages the next generation of manufacturing to be flexible, intelligent, and interoperable. The implementations of the Artificial Intelligence (AI) technology could potentially enhance maintenance in efficiency, and accuracy. However, it will not be a substitution to the human operator’s flexibility, decision-making and information received by the natural five senses. Augmented reality (AR) is commonly understood as a technology that overlays virtual information onto the existing environment to provide users a new and improved experience to assist their daily activities. However, AR can be used to enhance all human five senses rather than just overlay virtual imagery. In this paper, a design and a practical plan of smell augmentation for diagnosis is initialised, via a case study in maintenance. The aim of this paper is to evaluate the feasibilities, identify challenges, and summarise initial results of overlaying information through smell augmentations.
Keywords: Augmented Reality (AR); Smell Augmentation; Maintenance